The Influence of Service Quality, Products, Promotions, and Store Atmosphere on Customer Satisfaction at Café Jm 77 Rantauprapat - Halawa, Esiska Br; Elvina, Elvina; Halim, Abd. (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This type of research is quantitative, the place for this research is Café JM 77 Rantauprapat. Because the population in this study is unknown, the Lemeshow formula was used to determine the sample size. So, the total number of respondents in this study was 96 customers at Café JM 77 Rantauprapat. The data collection techniques used in the research were observation, documentation, and questionnaires using a Likert scale. This research uses classical assumption tests which include the data normality test, heteroscedasticity test, and multicollinearity test. Multiple linear regression analysis was tested using partial (t), simultaneous (F), and coefficient of determination tests. The partial and simultaneous research results show that the variables of service quality, product, promotion, and store atmosphere have a positive and significant effect on customer satisfaction at Café JM 77 Rantauprapat.